EFEKTIVITAS PELAKSANAAN PROGRAM PEMBANGUNAN BERBASIS RUKUN TETANGGA DI KABUPATEN SUMBAWA BARAT TAHUN 2014 – 2015 - Yudhi Lestanata; Ulung Pribadi (Universitas Muhammadiyah Yogyakarta, 2016)
Focused on the development system capacity and capability of the public has a strong resistance when hit byproblems. PBRT program is an instrument to encourage the realization of economic, social, political andcultural as well as a means of social transformation that is expected to be able to boost the slump situation andconditions of the community that had developed over time. This innovation is quite interesting and unique,because it is the only model of development in the province ntb even in Indonesia. The approach used in thisstudy is deductive method qualitative descriptive analysis. This type of research tried to describe the actualpicture of the phenomenon occurring in the management of the Neighborhood Program Based in WestSumbawa regency. From hasi research note that based development program Rukun Tetagga being featuredprogram and the pilot program the West Sumbawa regency was not effective as expected. From the datafindings during authors examined the field can see that the program is one of the important innovations of WestSumbawa Regency in boosting success in the development of this pogram set, but do not like innovation andhope in the rules for the way it turned out this program has not been effective. Many existing resources thatare not in manfaatkan.penulis hope that this program still exist and revived the spirit of development actors inmaximizing this PBRT program.